Assessment of the Perception of Malaria Prevention among Pregnant Women Attending Antenatal Clinic at Obiozara Health Center Uburu, Ohaozara, Ebonyi State (Lafia Journal of Scientific and Industrial Research, 2025)
Malaria infection during pregnancy remains a serious public health concern in tropical and subtropical regions, threatening the wellbeing of mothers, fetuses, and newborns. In Nigeria, it remains a leading cause of maternal mortality. This study investigated the perception of malaria prevention among pregnant women attending antenatal clinic at Obiozara Health Center, Uburu, Ohaozara, Ebonyi State. A descriptive cross-sectional design was used, involving 200 respondents (pregnant women attending the antenatal clinic at Obiozara Health Center, Uburu, Ohaozara, Ebonyi State). The study revealed a high level of awareness about malaria prevention among pregnant women, with 89.9% acknowledging that malaria during pregnancy is dangerous and preventable. The most commonly adopted preventive method was the use of mosquito coils and sprays (53%), followed by sleeping under insecticide-treated nets (96%), clearing bushes (35%), and destroying stagnant water (24%). However, a few respondents relied on ineffective or incorrect practices such as eating well, avoiding sunlight, or drinking herbal mixtures. The major challenges identified in malaria prevention were economic and behavioral factors, including the inability to afford mosquito nets (16%) and discomfort associated with sleeping under them (22%). Based on these findings, the study recommended improving the affordability and comfort of malaria prevention methods by promoting locally suitable mosquito nets and encouraging consistent use. It also suggested targeted community education to dispel misconceptions about malaria causes and prevention.
Keywords: Malaria during pregnancy; antenatal clinic; pregnant women; mosquito nets; trimester